Global Epidemiology and Phenotypic Diversity of 21-Hydroxylase–Deficient Congenital Adrenal Hyperplasia: A 25-Year Comparative Review Across Ethnicities, Genotypes, and National Cohorts: Global Epidemiology of 21-Hydroxylase CAH - Nada Soliman; Ashraf T. Soliman; Fawzia Alyafei; Shayma Ahmed; Noor Hamed; Nada Alaaraj; Shaymaa Elsayed; Dina Fawzy; Ahmed Elawwa (International Journal of Public Health Excellence (IJPHE), 2026)
Congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency (21-OHD) represents the most common inherited disorder of adrenal steroid biosynthesis worldwide. Over the past 25 years, advances in newborn screening, molecular diagnostics, and genotype–phenotype characterization have produced large shifts in the global epidemiological landscape. However, marked disparities persist between countries and ethnic groups, reflecting founder mutations, consanguinity, migration patterns, and differences in healthcare coverage. Exclusion criteria included mixed-etiology CAH without subtype separation and cohorts lacking validated genetic testing. Quality assessment relied on established criteria for observational epidemiology and registry-based studies. Birth prevalence showed extreme global heterogeneity, ranging from 1:23,000 in New Zealand to 1:1,200 in Egypt and as high as 1:282 among Arctic Indigenous founder populations. Ethnicity strongly influenced incidence, with Asian, Hispanic/Latino, and European populations generally displaying moderate rates (5–10 per 100,000 births), while Middle Eastern and North African populations demonstrated markedly higher incidence due to elevated consanguinity rates and clustering of severe CYP21A2 alleles. Cross-country phenotype analysis revealed that salt-wasting predominated in Egypt, China, India, Turkey, Argentina, and several Eastern European cohorts, whereas European cohorts—especially Portugal and the UK—showed higher proportions of nonclassic or milder phenotypes. Genotype–phenotype mapping demonstrated consistent associations: null and severe Group A mutations with the SW phenotype, I2 splice and I172N variants with SV presentations, and V281L with NC disease. Sex differences were notable: females more commonly presented in infancy due to virilization, while males frequently remained undetected until adrenal crises or testicular adrenal rest tumors. National screening programs significantly shifted age of diagnosis and reduced infant morbidity and mortality. Global epidemiology of CAH continues to display substantial geographic and ethnic variability, driven by population genetics, healthcare disparities, and screening strategies. Understanding these differences is essential for improving early detection, tailoring genotype-informed care, guiding newborn screening expansion, and reducing long-term complications